La novela de Carlos Tomatis - Juan Carlos Mondragón (Cuadernos LIRICO)
The objective of this work is to study the novel/character mechanism as an encounter between fiction and narrative strategies. The idea is to prove that this duality can turn out to be, in Saer’s work, a mechanism for gaining literary legitimacy. In that context, Lo imborrable is considered a central piece of this complex device, and Carlos Tomatis, a privileged passenger of “the work” that the writing of his family novel acquires in the aforementioned text.